Uji Antagonisme Jamur Trichoderma sp. terhadap Rigidoporus lignosus Asal Tanaman Karet secara In Vitro - Desianty Dona Normalisa Sirait; Sry Ekanitha Pinem (Universitas Sebelas Maret, 2022)
White root rot disease (Rigidoporus lignosus) is one of the main diseases in rubber plants that can cause death the plants. Trichoderma sp. known as one of the biological control agents that capable of controlling the disease. This research aimed to identify the the potential of Trichoderma sp. isolates in controlling white root disease Rigidoporus lignosus in vitro. Trichoderma sp. isolates were isolated from 7 (seven) smallholder rubber plantations. The locations were Serdang Bedagai, Langkat, Simalungun, Labuhan Batu, Batubara, Asahan and Labuhan Batu districts. The seven Trichoderma sp. isolates were antagonized with Rigidoporus lignosus isolates from 4 (four) smallholder rubber plantations i.e from Serdang Bedagai, Langkat, Simalungun and Labuhan Batu districts. The antagonisme methods used dual culture on Potato Dextrose Agar (PDA) medium.The lowest inhibition zone in single treatment came from isolates from Simalungun district (TS) of 79.91% and the highest was isolate from Asahan district (TA) which was 91.82%. In combination treatment Trichoderma sp. isolate from Asahan (TA) could inhibit R. lignosus isolate from Serdang Bedagai (JSB), Simalungun (JS) and Labuhan (JLB) 100%. Trichoderma sp. isolate from Batubara (TB) could inhibit R. lignosus isolate from Langkat (JL), Simalungun (JS) and Labuhan (JLB) 100%. All of Trichoderma sp. isolates had potential biological control agents, but in this research only both Trichoderma sp. isolates from Asahan (TA) and Batubara (TB) could inhibit most of the R. lignosus isolates in vitro.